Design for community : the art of connecting real people in virtual places - Powazek, Derek M. (New Riders, 2002)
This book is available as an Adobe Reader eBook on the publisher's website: newriders.com Communities are part of all successful web sites in one way or another. It looks at the different stages that must be understood: Philosophy: Why does your site need community? What are your measures of success? Architecture: How do you set up a site to createpositive experience? How do you coax people out of their shells and get them to share their experiences online? Design: From color choice to HTML, how do you design the look of a community area? Maintenance: This section will contain stories of failed web communities, and what they could have done to stay on track, as well as general maintenance tips and tricks for keeping your community "garden" growing.